A study of prevalence of Vitamin D deficiency among pregnant women and its impact on feto maternal outcome - Nageshu, Shailaja; Krishna, Kirtan; L., Krishna; Bhat, B. Shyamasundara; Suma, H. R.; Reddy, Surekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of our study was to determine the prevalence of vitamin D among pregnant women and its impact on feto maternal outcome. Methods: An observational study was conducted among 80 pregnant women at PESIMSR, Kuppam over a period of one month from first September 2014 to 30th September 2014. Our primary outcome was to study prevalence of Vitamin D deficiency in pregnant women and secondary outcome to study maternal and fetal outcome in pregnant women with Vitamin D deficiency. The subjects participating in the study were requested to complete a questionnaire that covered socio-demographic data, religion, obstetric history, lifestyle, dietary habits and psychosocial factors. Reliable serum 25-hydroxyvitamin D (25(OH) D) level was measured using an enzyme immunoassay method in the extra nine ml blood sample. Data on date of delivery, baby sex, birth weight, length and gestational age (based on ultrasound or on the timing of the last menstrual period) were collected prospectively. Results: In the study period of the 80 women recruited, 3.8% were Christians, 78.8% were Hindus and 17.4% were Muslims. All women recruited for the study were >32 wks gestation. It was found that 53.8% had insufficient serum 25 (OH) D concentrations and 13.8% were deficient for vitamin D. The lowest 25(OH) D concentrations (insufficient levels) were found in those with only one-two hours of sun exposure (65.1%), and 54.5% had deficient levels. Highest concentrations (11.5%) were found in those with two-four hours of sun exposure. There were no significant associations between 25(OH) D concentrations and maternal outcome. The analysis showed a significant association between a deficient vitamin D status (45.5%) and low birth weight (<2.5Kg) compared to 15.4% who had normal vitamin D levels. An insufficient vitamin D status was also related to a lower birth weight, but the association was not statistically significant. Among babies born to study subjects 84.6% had a normal birth weight of 2.5-3.5 kg with normal maternal vitamin D levels, when compared to 36.4% with deficient maternal vitamin D levels. We did not find any significant association between Vitamin D levels and neonatal complications. Conclusions: In our pilot study we found that prevalence of vitamin D deficiency was very high. Our sample size was too small to comment on impact of vitamin D deficiency on fetomaternal outcome. Hence we stopped our study and considered universal supplementation to all pregnant women.